A new megasport legacy : host-country human rights and anti-corruption reforms - Spalding, Andrew Brady (New York, NY : Oxford University Press, 2022)
Megasports are now demonstrating a capacity to leave what this book calls a human rights and anti-corruption legacy: norms, practices, policies, or laws that have application beyond sport, are likely to endure after the event, and the implementation of which is accelerated by hosting the event. This book analyzes existing megasport policies and practices, then suggests reforms to acknowledge and support these new legacies.
Also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on April 8, 2022).
Keywords: Sports -- Sociological aspects; Human rights movements; Human rights in sports; Sports -- Corrupt practices -- Prevention; Sports and state